Analisa Kinerja Sistem Radio Over Fiber (ROF) Menggunakan Teknik Quadrature Amplitude Modulation (QAM) Untuk Jaringan Wireless Local Area Network (WLAN) - Halimah, Nikmatul; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The development of data telecommunications with high speed and wide coverage is currently getting higher and higher. Therefore a reliable network can provide a network with large bandwidth and capacity which is called Radio Over Fiber (ROF). Radio Over Fiber (ROF) is a combination of Radio Frequency (RF) and optical fiber-based communication, where ROF uses optical fiber as an intermediary medium. This study designed a ROF that operates at a frequency of 5.8 GHz using Quadrature Amplitude Modulation (QAM) techniques for the application of Wireless Local Area Network (WLAN). The parameters considered in this research simulation are the value of BER, Q-Factor, and eye diagram using optisystem software. Based on the results of the analysis, the best BER on the 8-QAM modulation technique with a distance of 50 km is 9.02362 x 10-13 and the Q-Factor is 7.00782. Keywords: Radio Over Fiber, Bit Error Rate, Q-Factor, QAM, WLAN